The impact of monetary policy announcements on the stock price of large European banks during the financial crisis - Ricci, Ornella (Journal of Banking & Finance, 2015)
Since 2007, the European Central Bank responded decisively to the challenges posed by the global financial crisis, reducing key policy interest rates to unprecedented low levels and intervening with non-standard policy measures (i.e., monetary easing and liquidity provision). This paper aims to assess the impact of ECB monetary policy announcements on the stock price of large European banks. As a first step, an event study is conducted in order to measure cumulated abnormal returns (CARs) around the announcements over June 2007–June 2013; the second step is a regression analysis aimed at identifying the determinants of CARs. Results show that banks were more sensitive to non-conventional measures than to interest rate decisions, and that the same type of intervention may have a different impact depending on the stage of the crisis. In addition, banks with weaker balance sheets and operating with high-risk were more sensitive to monetary policy interventions.